The microbiome and allergic diseases - Renz, Harald (Henry Stewart Talks, 2024)
Immune tolerance and breakdown of tolerance, Microbial signature is influenced by maternal, lifestyle, and environmental factors, Postnatal risk factors for the development of allergy and asthma, Short-chain fatty acids (SCFA), Prebiotics, probiotics, and postbiotics, Diet, microbes, and immune modulation, Depleted microbial diversity and increased chronic inflammation